2015
DOI: 10.2460/ajvr.76.8.724
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between intracranial pressure as measured by an epidural intracranial pressure monitoring system and optic nerve sheath diameter in healthy dogs

Abstract: ICP was positively and nonlinearly associated with increasing maximum ONSD, especially when ICP was ≤ 20 mm Hg above baseline, supporting the conclusion that ultrasonographic measurement of maximum ONSD may provide a noninvasive monitoring tool for evaluation of ICP in dogs. Further research is needed to assess the utility of these measurements in clinical patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 30 publications
0
25
0
2
Order By: Relevance
“…One study showed that the relationship of intracranial pressure to optic nerve sheath diameter was slightly nonlinear with optic nerve sheath diameter increased more in the early stages of intracranial hypertension. 36 On the other hand, another study demonstrated that the relationship between TCD vascular resistance variables and intracranial pressure was linear in dogs. 20 This discrepancy might be due to different effects of intracranial pressure on cerebral blood flow and optic nerve sheath size.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One study showed that the relationship of intracranial pressure to optic nerve sheath diameter was slightly nonlinear with optic nerve sheath diameter increased more in the early stages of intracranial hypertension. 36 On the other hand, another study demonstrated that the relationship between TCD vascular resistance variables and intracranial pressure was linear in dogs. 20 This discrepancy might be due to different effects of intracranial pressure on cerebral blood flow and optic nerve sheath size.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to TCD, various noninvasive methods for assessment of intracranial pressure have been applied to dogs . The combination of MRI findings is useful and reliable for the diagnosis of intracranial hypertension in dogs .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations